Symposium 3: Evocative writing and lived experience descriptions for networked learning research - Lee, Kyungmee (Proceedings of the International Conference on Networked Learning, 2024)
The present paper introduces evocative writing, advocated by autoethnographies, as an effective research method to capture the subtleties of real-life networked learning experiences, enabling researchers to observe and make sense of both the beautiful and the ugly of the phenomenon. Evocative writing practice can liberate researchers from the established academic tradition that unnecessarily devalues their subjectivity and limits their creativity by imposing the problematic normality of research objectivity. Writing is a central research act that needs to be successfully performed throughout the entire research project—not only to present project outcomes but also to formulate research problems, collect data, and validate outcomes. Despite its aesthetic and communicative merits, however, evocative researchers as human beings cannot fully grasp the structural essence of the lived experiences of networked learning phenomena beyond their own frame of reference. Here, the author believes that lived experience descriptions and related methodological techniques devised by phenomenologists can provide evocative networked learning researchers with a possible breakthrough. Based on the author’s own experiences, the author will demonstrate the effective use of evocative writing complemented by lived experience descriptions for networked learning research.